2017
DOI: 10.1007/s12033-017-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

Host-Induced Silencing of Pathogenicity Genes Enhances Resistance to Fusarium oxysporum Wilt in Tomato

Abstract: This study presents a novel approach of controlling vascular wilt in tomato by RNAi expression directed to pathogenicity genes of Fusarium oxysporum f. sp. lycopersici. Vascular wilt of tomato caused by Fusarium oxysporum f. sp. lycopersici leads to qualitative and quantitative loss of the crop. Limitation in the existing control measures necessitates the development of alternative strategies to increase resistance in the plants against pathogens. Recent findings paved way to RNAi, as a promising method for si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The mutant strain displayed comprehensive loss of virulence, and characterization of the insertion site revealed inactivation of the chsV gene. These findings suggest that the chsV gene is necessary to resist the defense compounds, a prerequisite for pathogenicity (Bharti et al, 2017).…”
Section: Virulence Genes Requirements For the Pathogenicity Of Folmentioning
confidence: 99%
“…The mutant strain displayed comprehensive loss of virulence, and characterization of the insertion site revealed inactivation of the chsV gene. These findings suggest that the chsV gene is necessary to resist the defense compounds, a prerequisite for pathogenicity (Bharti et al, 2017).…”
Section: Virulence Genes Requirements For the Pathogenicity Of Folmentioning
confidence: 99%
“…In addition to the generation of RNA-silencing signals in planta, plants can be protected from pathogens and pests by spray-applied RNA biopesticides designated as spray-induced gene silencing (SIGS) (Koch et al, 2016;Wang et al, 2016;Konakalla et al, 2016;Mitter et al, 2017a;Kaldis et al, 2018;Koch et al, 2019). Regardless of how target-specific inhibitory RNAs are applied (i.e., endogenously or exogenously), the use of HIGS and SIGS technologies to control Fusarium species have been shown to be a potential alternative to conventional pesticides (Koch et al, 2013;Ghag et al, 2014;Cheng et al, 2015;Hu et al, 2015;Chen et al, 2016;Pareek and Rajam, 2017;Bharti et al, 2017;Baldwin et al, 2018;Koch et al, 2018Koch et al, , 2019 supporting the notion that RNAi strategies may improve food safety by controlling the growth of phytopathogenic, mycotoxin-producing fungi (reviewed by Majumdar et al, 2017;Machado et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al (2015) successfully improved resistance of wheat against Fusarium graminearum pathogen that causes Fusarium head blight and Fusarium seedling blight by silencing of the fungal virulence gene chitin synthase 3b ( Chs3b ) through HIGS. Similarly, Bharti et al (2017) demonstrated host induced silencing of FOW2 and chsV genes in Fusarium oxysporum in transgenic tomato plants conferring enhanced resistance to vascular wilt disease. Recently, Song and Thomma (2018) through host-induced silencing of Ave1, Sge1 and NLP1 genes of Verticillium dahliae created tomato and Arabidopsis plants resistant to Verticillium wilt disease.…”
Section: Discussionmentioning
confidence: 93%
“…Since last ten years, HIGS strategy is widely employed to control plant diseases via suppression of pathogen infection by targeting and silencing a variety of pathogen genes to disable pathogen development/differentiation and pathogenicity (Bharti et al , 2017; Chen et al , 2016; Ghag et al , 2014; Jahan et al , 2015; Koch et al , 2013; Nowara et al , 2010; Song and Thomma, 2018; Thakare et al , 2017). These studies showed that selection of appropriate target gene(s) is the most important requirement for developing an effective HIGS to incapacitate fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%